BF‐200 ALA gel vs. MAL cream for BCC. (1st August 2018) - Morton, C.A.; Dominicus, R.; Radny, P.; Dirschka, T.; Hauschild, A.; Reinhold, U.; Aschoff, R.; Ulrich, M.; Keohane, S.; Ekanayake‐Bohlig, S.; Ibbotson, S.; Ostendorf, R.; et al.
Summary: Basal cell carcinoma (BCC), also known as rodent ulcer, is the most common type of non‐melanoma skin cancer worldwide. It affects about 3–10% of people. This study from the U.K. and Germany aimed to find out if BF‐200 ALA gel would work as well as (is non‐inferior to) the already authorised MAL cream in the treatment of non‐aggressive BCC lesions. Both medications are applied topically (on the skin) to the tumour, which is then illuminated with a certified lamp. The illumination causes a chemical reaction that affects the cancer cells so that they eventually die. This kind of procedure is called photodynamic therapy (PDT). Patients in the study were put into the two groups by chance (randomized): 138 in the BF‐200 ALA group and 143 in the MAL group. The treatment scheme for both drugs was the same. Initially, patients had two PDTs one week apart. Four and 12 weeks after the second PDT, patients visited the doctor again, who assessed the treated lesions and patient's health. If all lesions were gone by week 12, the patient entered the 5‐year follow‐up study. In case of remaining lesions, patients received two more PDTs before entering the follow‐up. During the follow‐up, doctors monitor the health of the patients and assess if any of the treated lesions come back. The study found that there was no difference between the two groups, which means that BF‐200 ALA gel worked as well as the already approved MAL cream. In 113 of 121 patients (93.4%) treated with BF‐200 ALA and 101 of 110 patients (91.8%) treated with MAL, lesions disappeared completely. 87% of the BF‐200 ALA‐treated patients rated their satisfaction with the PDT as "very good or good"; 86% of the MAL‐treated patients said the same. Almost all patients experienced mild to moderate local side effects related to the study medications. Common side effects at the application site, which affected more than 1 of 10 patients, were pain, skin reddening (erythema), itching (pruritus), and tissue swelling (oedema). Side effects were similar for both medications. At 12‐month follow‐up, lesions reappeared in 8.4% of the BF‐200 ALA‐treated patients and in 8.5% of the MAL‐treated patients. The follow‐up is still ongoing; further results will be reported after the end of the study. This study showed that BF‐200 ALA gel is as effective and well‐tolerated as MAL cream in the treatment of non‐aggressive BCC. Based on these findings, the European Medicine Agency (EMA) granted approval for BF‐200 ALA for the treatment of non‐aggressive BCC.